2018
DOI: 10.3390/ijms19113672
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition and Metastasis under the Control of Transforming Growth Factor β

Abstract: Metastasis of tumor cells from primary sites of malignancy to neighboring stromal tissue or distant localities entails in several instances, but not in every case, the epithelial-mesenchymal transition (EMT). EMT weakens the strong adhesion forces between differentiated epithelial cells so that carcinoma cells can achieve solitary or collective motility, which makes the EMT an intuitive mechanism for the initiation of tumor metastasis. EMT initiates after primary oncogenic events lead to secondary secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 169 publications
(271 reference statements)
3
124
0
2
Order By: Relevance
“…These similarities were also consistent with a recent study on TNBCs showing that the expression of ZEB1, and not the expression of advanced mesenchymal markers, was specifically correlated with poor clinical outcome (Jang et al, 2015). Interestingly, the stimulation with TGFβ induced a distinct phenotype, with a strong contractility and clear polarization toward the extracellular matrix, even though the TGFβ pathways proceed via the induction of ZEB1 (Tsubakihara and Moustakas, 2018). We interpreted the differences between the E/M-state and M-state in our experimental models as the consequence of the activation of the RhoA pathway, which is also downstream of TGFβ (Bhowmick et al, 2001;Kardassis et al, 2009;Tavares et al, 2006) (Figure 5 and Supplementary figure S3).…”
Section: Discussionsupporting
confidence: 89%
“…These similarities were also consistent with a recent study on TNBCs showing that the expression of ZEB1, and not the expression of advanced mesenchymal markers, was specifically correlated with poor clinical outcome (Jang et al, 2015). Interestingly, the stimulation with TGFβ induced a distinct phenotype, with a strong contractility and clear polarization toward the extracellular matrix, even though the TGFβ pathways proceed via the induction of ZEB1 (Tsubakihara and Moustakas, 2018). We interpreted the differences between the E/M-state and M-state in our experimental models as the consequence of the activation of the RhoA pathway, which is also downstream of TGFβ (Bhowmick et al, 2001;Kardassis et al, 2009;Tavares et al, 2006) (Figure 5 and Supplementary figure S3).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, 4T1 monolayers expressed low levels of EMT associated transcription factors Snai1, Zeb1 and Twist1. In contrast, EMT markers Krt14, Trp63, and Grhl2, which have been recently shown to correspond to an early hybrid state [25], were significantly up-regulated solely in in vivo conditions. However, late hybrid Smad3 and mesenchymal marker Mmp19 were significantly up-regulated in both 3D and in vivo conditions suggesting that tumors in vivo reside in more diverse EMT hybrid states.…”
Section: Culturing Condition Affects Cancer Cell Behavior Critical Tomentioning
confidence: 73%
“…Recent studies have demonstrated that the EMT is a common molecular mechanism in PDAC 14 and a vital process in cancer progression and metastasis 15,16 through which cancer cells acquire invasive properties. Our results indicated that SPOCK1 has strong tumorigenic activity in vitro and in vivo and promotes PDAC cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%